Weight control in wrestling: eating disorders or disordered eating? - Dale, K. S.; Landers, D. M. (Medicine & Science in Sports & Exercise, 1999)
PURPOSE: Several recent studies have pointed out that the weight loss techniques used by wrestlers to make weight are similar to the behavior of bulimics. The purpose of this study was to determine whether an increased risk of bulimia nervosa existed for a group of junior high and high school wrestlers. METHODS: Wrestlers (N = 85) completed the Eating Disorder Inventory (EDI) once during the season, and once during the off-season. A comparison group of nonwrestlers (N = 75) also completed the questionnaire. RESULTS: No significant differences were found between the number of in-season wrestlers and nonwrestlers classified as "at risk" for bulimia nervosa. Significant differences were revealed, however, between in-season wrestlers and nonwrestlers, and between in-season wrestlers and off-season wrestlers, on the Drive for Thinness subscale. In both cases, significantly more in-season wrestlers scored above the "at risk" cutoff on the subscale. CONCLUSIONS: These results indicate that although in-season wrestlers are more weight conscious than nonwrestlers, these feelings and attitudes are transient. All subjects classified as "at risk" also participated in an interview which followed the format of the Eating Disorder Examination. Interviews with in-season wrestlers revealed that their concerns with weight were due entirely to the demands of wrestling, and did not meet the severity level required for a diagnosis of bulimia nervosa.